FAKTOR RISIKO KEJADIAN LOW BACK PAIN (LBP) PADA PEKERJA LAUNDRY DI DESA GENTAN, BAKI, SUKOHARJO: RISK FACTORS OF LOW BACK PAIN (LBP) INCIDENCE AMONG LAUNDRY WORKERS IN THE VILLAGE OF GENTAN, BAKI, SUKOHARJO - waluyo, sunaryo joko (Politeknik Insan Husada Surakarta, 2024)
ABSTRACT Introduction: Low Back Pain (LBP) is a common health issue among workers, including those in the laundry industry. The occurrence of LBP can have negative impacts on productivity and worker well-being. Thus, this study aims to identify the risk factors associated with LBP among laundry workers in the village of Gentan, Baki, Sukoharjo. Method: This study utilizes a quantitative approach with a descriptive research design. The sample consists of laundry workers employed in the village of Gentan, Baki, Sukoharjo. Data were collected through a questionnaire that assessed the risk factors related to LBP. Descriptive statistics were employed to analyze the data. Results: The findings reveal that excessive workload and ergonomic risks are significant factors associated with LBP among laundry workers. Workers often face high job demands, including limited time to complete tasks and handling heavy items. Additionally, non-ergonomic work conditions contribute to the occurrence of LBP. Conclusion: This study emphasizes the importance of identifying and managing the risk factors associated with LBP among laundry workers. Measures such as reducing excessive workload and improving non-ergonomic work conditions can help mitigate the risk of LBP. Long-term preventive efforts should be implemented to ensure the health and well-being of laundry workers. Consequently, this research provides valuable insights for stakeholders in enhancing the well-being of laundry workers and reducing the occurrence of LBP. Keywords: Low Back Pain, Laundry workers, Risk factors.